(1282) International market of African professional skills-A comparative study السوق الدولية للمهارات المهنية الأفريقية - دراسة مقارنة - Kheiralla, Raiga Abdin (The Institute Of National Planning., 2018)
One noteworthy aspect of international migration in the last two decade has been the systemic transfer of same labour force between different countries. Actual movement of profesionals is only one aspect of integration into the international market. In order to move, certainly, a professional must be mobile, that is an possession of internationally negotiable qualifications.